Evaluation of the coefficient of variation as a measure of precision to the experiments with citrus - Amaral, Alexandre Morais do; Muniz, Joel Augusto; Souza, Maurício de (Pesquisa Agropecuaria Brasileira, 1997)
The present study was developed with values of coefficients of variation (CV) taken from various works published in Brazil, with emphasis on fruit culture, and their variables most currently studied (height and fruit production per plant; diameter and fruit weight; yield, pH, "ratio", soluble solids and juice acidity). The objective was to propose CV bands which orient the researcher in the evaluation of each variable. After data grouping, a test of normality of Lilliefors was made, which revealed that all the variables utilized had an approximately normal distribution. With this, by means of a table based on work with forest species which establishes the medium and the standard deviation [CV±√Var(CV)], a table was constructed with suggested intervals of CV for each variable in question. The number of fruits per plant variable was that which presented larger coefficient values, and the values related to the juice (obtained in the laboratory) were those which generally presented the smaller CV.